Mutu Pendidikan dipengaruhi signifikan oleh Kurikulum dan Bahan Ajar (studi di Sekolah Polisi Negara Polda Jawa Barat) - Itto Turyandi (Program Studi Manajemen, Universitas Al Ghifari, 2021)
The quality of education in the West Java Police State Police School is still low, it is presumably caused by the application and update the curriculum and teaching materials that have not been optimal. Based on the above, the researcher conducting research on aspects that affect the quality of education, especially from the aspect of curriculum and teaching materials.The methodology used is descriptive verification by using the technique of path analysis (path analysis) in order to know the effect of direct and indirect influence to get the coefficient of determination.The results showed that the quality of education in the West Java Police State Police School is directly affected by the curriculum of 18.83% and is affected by the indirect influence of 10.75%, as well as that quality of education is affected directly by the teaching materials by 16.81% so total effect determination coefficient of 57.14%.The conclusion of this study that the quality of education in the West Java Police State Police School is influenced by the curriculum and teaching materials, and influenced by other educational components that are